FAM19A4/miR124-2 Methylation Testing and Human Papillomavirus (HPV) 16/18 Genotyping in HPV-Positive Women Under the Age of 30 Years. (10th June 2022) - Vink, Frederique J; Meijer, Chris J L M; Hesselink, Albertus T; Floore, Arno N; Lissenberg-Witte, Birgit I; Bonde, Jesper H; Pedersen, Helle; Cuschieri, Kate; Bhatia, Ramya; Poljak, Mario; Oštrbenk Valenčak, Anja; Hillemanns, Peter; et al.
Abstract: Background: High-grade squamous intraepithelial lesions (HSIL) or cervical intraepithelial neoplasia (CIN) grade 2/3 lesions in human papillomavirus (HPV)–positive women <30 years of age have high spontaneous regression rates. To reduce overtreatment, biomarkers are needed to delineate advanced CIN lesions that require treatment. We analyzed the FAM19A4/miR124-2 methylation test and HPV16/18 genotyping in HPV-positive women aged <30 years, aiming to identify CIN2/3 lesions in need of treatment. Methods: A European multicenter retrospective study was designed evaluating the FAM19A4/miR124-2 methylation test and HPV16/18 genotyping in cervical scrapes of 1061 HPV-positive women aged 15–29 years (690 ≤CIN1, 166 CIN2, and 205 CIN3+). A subset of 62 CIN2 and 103 CIN3 were immunohistochemically characterized by HPV E4 expression, a marker for a productive HPV infection, and p16 ink4a and Ki-67, markers indicative for a transforming infection. CIN2/3 lesions with low HPV E4 expression and high p16 ink4a /Ki-67 expression were considered as nonproductive, transforming CIN, compatible with advanced CIN2/3 lesions in need of treatment. Results: FAM19A4/miR124-2 methylation positivity increased significantly with CIN grade and age groups (<25, 25–29, and ≥30 years), while HPV16/18 positivity was comparable across age groups. FAM19A4/miR124-2 methylation positivity was HPV type independent. Methylation-positive CIN2/3 lesions had higher p16 ink4a /Ki-67-immunoscores ( P = .003) and expressed less HPV E4 ( P = .033) compared with methylation-negative CIN2/3 lesions. These differences in HPV E4 and p16 ink4a /Ki-67 expression were not found between HPV16/18–positive and non-16/18 HPV–positive lesions. Conclusions: Compared with HPV16/18 genotyping, the FAM19A4/miR124-2 methylation test detects nonproductive, transforming CIN2/3 lesions with high specificity in women aged <30 years, providing clinicians supportive information about the need for treatment of CIN2/3 in young HPV-positive women. Abstract : In young women, spontaneous regression of cervical intraepithelial neoplasia grade 2/3 (CIN2/3) is high and FAM19A4/miR124-2 methylation test positivity rate is low. The FAM19A4/miR124-2 methylation test detects CIN2/3 with nonproductive, transforming features, compatible with advanced CIN.